Publisher Correction: Performance of creatinine and cystatin C-based equations to estimate glomerular filtration rate in African children with sickle cell anemia...Nkoy AB, Mumaka FM, Matoka TT, et al. Pediatric Nephrology (PEDIATR NEPHROL). 2026;41(2):447-456. - Nkoy, Agathe Bikupe; Mumaka, Floreen Maluwenze; Matoka, Therance Tobo; Ngonde, Ange; Sumaili, Ernest Kiswaya; Bukabau, Justine Busanga; Labarque, Veerle; van den Heuvel, Lambertus P.; Bökenkamp, Arend; Cavalier, Etienne; Levtchenko, Elena; Delanaye, Pierre; et al. (Pediatric Nephrology, 2026)
The article addresses a correction to a previously published study in Pediatric Nephrology, specifically regarding the misrepresentation of figures in the original document. It clarifies that Figure 1 was displayed twice, with the second instance incorrectly labeled as Figure 2. The corrected figures are now provided to ensure accurate representation of the data. The publisher, Springer Nature, maintains a neutral stance on jurisdictional claims in published maps and institutional affiliations.